Early Weaning: a Management Alternative for Florida Beef Cattle Producers - John Arthington (EDIS)
Revised! AN-131, a 9-page illustrated fact sheet by John Arthington, describes this management practice involving the permanent separation of the cow and calf when the calf is 70 to 90 days of age. Published by the UF Department of Animal Sciences, May 2008.